ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN DAN TANTANGAN DALAM PENERAPAN PEMBELAJARAN BIOLOGI PADA SISWA MAN 1 MEDAN - Rifka Denisa Cibro; Alfi Nura Siregar; Damaiyani; Ennita Fauziah; Talita Salsabilah; Rizal Mukra; Widya Arwita (Jurnal Bionatural, 2026)
This study aims to analyze the use of instructional media and the challenges faced by teachers in implementing Biology learning for Senior High School (SMA) students. The research approach used is descriptive qualitative with Biology teachers at MAN 1 Medan as the research subjects. Data were collected through questionnaires, interviews, and observations, then analyzed using the Miles and Huberman interactive model which includes data condensation, data presentation, and drawing conclusions. The results of the study indicate that teachers have utilized various types of media, both conventional and technology- based such as videos, infocus, and teaching aids. However, the main obstacles faced are power  outages and limited teaching aids for practical activities. Teachers overcome these obstacles with alternative learning strategies such as learning outside the classroom and utilizing the surrounding environment as a real media. In general, the learning media used are in accordance with the scurriculum, but are not fully effective in improving student learning outcomes due to a lack of media variety and limited facilities. This study recommends the need for infrastructure improvements, teacher training in the use of digital media, and media innovations that are appropriate to student characteristics so that Biology learning becomes more interactive and meaningful.